Mechanism of solid/liquid interfacial reactions. Atomic force microscopy studies of the self-passivating reaction between solid p-chloranil and aqueous phase N,N-dimethylphenylenediamine - Booth, J; Compton, R; Atherton, J (1998)
The reaction between solid p-chloranil and alkaline aqueous solutions of dimethylphenylenediamine is shown to be self-passivating owing to the formation of insoluble product at the reacting interface. In situ atomic force microscopy imaging of the reaction occurring at (010) surfaces of single crystals of p-chloranil show that the nucleation of the overgrowth is progressive and that its coverage, S, follows the time (t) dependence S(t) = 1 - exp(-k3t3), where k3 is a rate constant. Measurement of the z piezo voltage throughout the reaction to give an absolute measure of the surface height shows that appreciable (hydroxide driven) dissolution occurs prior to the formation of the overgrowth and the surface becoming fully passivated.